Current Status of Soil-Transmitted Helminths among School Children in Kakamega County, Western Kenya. (20th July 2016) - Ngonjo, Teresia; Okoyo, Collins; Andove, Julius; Simiyu, Elses; Lelo, Agola Eric; Kabiru, Ephantus; Kihara, Jimmy; Mwandawiro, Charles
Abstract : Background. School age children are at high risk of soil-transmitted helminth (STH) worldwide. In Kenya, STH infections in children remain high despite the periodic administration of anthelmintic drugs. Our study assessed the prevalence and intensity of STH in primary school-aged children in Kakamega County, western Kenya. Methodology. We carried out a cross-sectional study on a population of 731 children attending 7 primary schools in March 2014. Children aged 4–16 years were examined for STH by the quantitative Kato-Katz technique. Infection intensities were expressed as eggs per gram (epg) of faeces. Findings. Among 731 school children examined for STH, 44.05% were infected. Highest prevalence of STH was in Shitaho primary school where 107 participants were examined and 62.6% were infected with mean intensity of 11667 epg. Iyenga had the least prevalence where 101 participants were examined and 26.7% were infected with mean intensity of 11772 epg. A. lumbricoides was the most prevalent STH species with 43.5% infected, while hookworm infections were low with 1.8% infected. Conclusion. Prevalence of STHs infections in Kakamega County remains high. We recommend guidelines and other control strategies to be scaled up to break transmission cycles.